Caffeine supplementation in the sport of futsal: How does it impact athletes’ endurance and speed? - Anggo Widcaksana Ilmawan; Ria Lumintuarso; Aulia Gusdernawati; Fitri Agung Nanda; Muhammad Tafwidh Alzaid (Journal Sport Area, 2023)
Endurance and speed are important components in supporting the success of futsal athletes. To increase this ability, many things can be done, one of which is to provide caffeine before exercising for maximum results. This study aims to determine the effect of caffeine on the endurance and speed of futsal athletes in Mataram. The research used is the type of experiment. In this study, the instrument for measuring endurance is the bleep test, while the speed is measured using the 100-meter sprint. This study is a population study because all populations are the research sample. The entire population is used in this study because all 16 samples are national athletes in the Vamos Mataram futsal group, and the research focuses on that one elite club. Data analysis was carried out using ANOVA with the help of SPSS. Based on the results of the data analysis of the futsal athletes of Vamos FC Mataram with the administration of caffeine, the significance value for endurance was 0.000 and the significance value for speed was 0.038. Based on the results of the significance test for the two variables having a value lower than 0.05, the data stated that there was an impact caused by caffeine administration to increase endurance and speed. The research has limitations, namely only focusing on one elite futsal club, namely Vamos Mataram, but the results are expected to be able to refer to the use of caffeine in an exercise program to be able to improve endurance and speed. Further research is expected to be able to cover more than one club as well as the addition of variables.